INTERELASI ALQURAN DAN KONSEP SOSIAL: KONSEPTUAL GOOD AND CLEAN GOVERNMENT SAID HAWWA DALAM AL-ASAS FI AT-TAFSIR - theo theojaka (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2019)
This research takes focus on how to conceptualize good and clean governance based on the universality of values ​​in the Qur'an, such as discussion, justice and equality which ultimately aims to lead to the concept of the baldatun state ṭayyibatun wa rabbun ghafūr as an ideal concept responding to the changing era. The description in this study takes a new form, namely thematic analysis with mufassir's view, Sa'id Hawwa in his interpretation in Al-Asas fi at-Tafsir. Data analysis is presented in the form of arguments or truth that can be justified scientifically and rationally related to siyasi verses. At the end of this study, the researcher analyzes that the basic framework is to build good and clean governance, which can accommodate corruption, collusion and nepotism by building internal relations between all social strata including people as holders of power, judges as enforcers of justice and leaders who carry out mandate of the people. The three stakeholders must be able to work together to present a sense of justice for all parties, be able to act according to the applicable law and realize that mutual benefit is a top priority. In its implementation, the Good and Clean Government must always place deliberations as the fundamental principles and philosophies of the country. In this case listed in the fourth precepts of Pancasila adopted by the Indonesian people.